Pengaruh penambahan konsentrasi cuka apel berbeda terhadap karakteristik kimia dan organoleptik kaldu ayam petelur afkir - Nadia Maharani; Irma Rahayu Ningrum; Muhammad Habbib Khirzin; Dewiarum Sari; Dwi Ahmad Priyadi (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
Laying hen meat is a food ingredient that contains high enough nutrition. The weakness of rejected laying hens is that the meat is very tough, so it is not accepted by most consumers. One way to make chicken meat attractive is to use it as processed broth. Chicken meat and bones contain high levels of minerals and fat, so you need to add apple cider vinegar to remove these substances. This study aims to determine the chemical quality (fat content, ash content, and pH) and organoleptic quality (color, taste, and aroma). This study used 4 treatments, namely P0 (0%), P1 (1%), P2 (2%), and P3 (3%) each repeated 4 times to obtain a total of 16 research samples. The designs used were Completely Randomized Design (CRD) and Randomized Block Design (RAK). The results showed that the average value of chemical quality parameters (fat content, ash content, and pH) along with the addition of the highest concentration of apple cider vinegar was produced by P3 of 3.25%, 0.37%, 5.89. The average organoleptic values ​​(color, taste, and aroma) along with the addition of the highest concentration of apple cider vinegar were produced by P3 of 4.48 in the category of creamy brown color, 4.36 in the category of meaty aroma, and 4.20 in the category of savory taste. It could be concluded that the addition of apple cider vinegar to the culled laying hen broth had a significant effect (P<0.05) on the chemical and organoleptic quality of the culled laying hen broth.